2016
DOI: 10.1002/art.39641
|View full text |Cite
|
Sign up to set email alerts
|

Reduced DICER1 Expression Bestows Rheumatoid Arthritis Synoviocytes Proinflammatory Properties and Resistance to Apoptotic Stimuli

Abstract: Objective While the regulatory role of individual microRNAs (miRNAs) in rheumatoid arthritis (RA) is well established, the role of DICER1 in the pathogenesis of the disease has not yet been investigated. The purpose of this study was to analyze the expression of factors involved in miRNA biogenesis in fibroblast‐like synoviocytes (FLS) from RA patients and to monitor the arthritis triggered by K/BxN serum transfer in mice deficient in the Dicer gene (Dicerd/d). Methods The expression of genes and precursor miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Furthermore, the recognition of the DICER1/ Alu RNA axis as a more general mechanism of pathogenesis could inspire a new view in other pathologic conditions in which DICER1 and/or Alu RNA are involved. Indeed, DICER1 deficit has also been observed in Parkinson’s disease, 37 in rheumatoid arthritis 38 and, recently, increase of Alu like elements was found to be associated with a Dicer1 decrease in a murine model of proliferative retinopathy. 39 …”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the recognition of the DICER1/ Alu RNA axis as a more general mechanism of pathogenesis could inspire a new view in other pathologic conditions in which DICER1 and/or Alu RNA are involved. Indeed, DICER1 deficit has also been observed in Parkinson’s disease, 37 in rheumatoid arthritis 38 and, recently, increase of Alu like elements was found to be associated with a Dicer1 decrease in a murine model of proliferative retinopathy. 39 …”
Section: Discussionmentioning
confidence: 91%
“…In contrast, the Dicer1 Gt(β-geo)Han mouse line, hereafter referred to as Dicer1 d/d , harbors a gene trap insertion in intron 24 of the Dicer1 locus, which results in a functional reduction in Dicer1 expression by ∼80% (25). The Dicer1 d/d line is viable, with susceptibility to viral infections, exacerbated experimental rheumatoid arthritis, and infertility due to insufficient corpus luteal angiogenesis among its reported phenotypes (25)(26)(27)(28)(29). Consistent with its C57BL/6J background, Dicer1 d/d did not exhibit hallmark features of the rd8 mutation, a prevalent confounder of retinal phenotypes (30).…”
Section: Genetic Deficiency Of Dicer1 Induces Spontaneous Rpe Atrophymentioning
confidence: 92%
“…This condition occurs as a result of the interaction between genetic and environmental cues, as genetic variants and epigenetic alterations increase the risk of developing the disease [ 127 , 128 , 129 ]. Dicer mRNA expression has been found to be significantly reduced in fibroblast-like synoviocytes (FLSs) of patients but not in isolated peripheral blood mononuclear cells (PBMCs) [ 130 ], a fact that indicates that differential Dicer expression in patients is located in specific cells ( Figure 6 ). The latter observations are supported by a study on another group of RA patients that also revealed no statistically significant Dicer expression difference in PBMCs when compared to that of healthy individuals [ 131 ].…”
Section: Dicer In Human Diseasesmentioning
confidence: 99%
“…Thus, Dicer might contribute to the pathogenesis by controlling the differential expression of several miRNAs in RA patients, leading to the regulation of immune response, cell cycle and apoptosis [ 132 , 133 ]. Experimental data from mouse models with limited expression of Dicer did not demonstrate an inflammatory phenotype at first, but a significant increase of joint inflammation was observed after the injection of K/BxN sera, which can induce arthritis in normal mice [ 130 ]. Thus, it seems that the absence of Dicer may not be responsible for the occurrence of the disease but for its progression, as the patients may fail to recover from a severe inflammation.…”
Section: Dicer In Human Diseasesmentioning
confidence: 99%
See 1 more Smart Citation